Find 5 0 5 0 ∫ 0 1 ( 1 − x 5 0 ) 1 0 1 . d x ∫ 0 1 ( 1 − x 5 0 ) 1 0 0 . d x
Details - This problem was asked in IIT examination
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
there is something wrong in the first step. applying by parts does not bring me to these steps.
Log in to reply
Once again Just Check @aditya vikram
Log in to reply
got it just, i was not applying the limits properly.
Nice solution!
Just a thing in the problem statement: you forgot the d x , Btw how do you write at the middle of the line??
Log in to reply
that's understood , thank you anyway , i am not understanding your last statement @hasan kassim
A = 5 0 5 0 ∫ 0 1 ( 1 − x 5 0 ) 1 0 1 d x ∫ 0 1 ( 1 − x 5 0 ) 1 0 0 d x
In both integrals, use substitution u = x 5 0 to get :
A = 5 0 5 0 ∫ 0 1 u − 5 0 4 9 ( 1 − u ) 1 0 1 d u ∫ 0 1 u − 5 0 4 9 ( 1 − u ) 1 0 0 d u
(Recall Beta Function properties.)
= 5 0 5 0 B ( 5 0 1 , 1 0 2 ) B ( 5 0 1 , 1 0 1 ) = 5 0 5 0 Γ ( 5 0 1 + 1 0 2 ) Γ ( 5 0 1 ) Γ ( 1 0 2 ) Γ ( 5 0 1 + 1 0 1 ) Γ ( 5 0 1 ) Γ ( 1 0 1 )
= 5 0 5 0 ( 5 0 1 + 1 0 1 ) Γ ( 5 0 1 + 1 0 1 ) Γ ( 5 0 1 ) ( 1 0 1 ) Γ ( 1 0 1 ) Γ ( 5 0 1 + 1 0 1 ) Γ ( 5 0 1 ) Γ ( 1 0 1 ) = 5 0 5 1
( Γ ( x + 1 ) = x Γ ( x ) )
Problem Loading...
Note Loading...
Set Loading...
x = 5 0 5 0 ∫ 0 1 ( 1 − x 5 0 ) 1 0 1 ∫ 0 1 ( 1 − x 5 0 ) 1 0 0
applying by parts in the denominator and then putting the limits we get
∫ 0 1 x 5 0 ( 1 − x 5 0 ) 1 0 0 ∫ 0 1 ( 1 − x 5 0 ) 1 0 0
= ∫ 0 1 ( 1 − ( 1 − x 5 0 ) ) ( 1 − x 5 0 ) 1 0 0 ∫ 0 1 ( 1 − x 5 0 ) 1 0 0
= ∫ 0 1 ( 1 − x 5 0 ) 1 0 0 − ∫ 0 1 ( 1 − x 5 0 ) 1 0 1 ∫ 0 1 ( 1 − x 5 0 ) 1 0 0
= 1 − ∫ 0 1 ( 1 − x 5 0 ) 1 0 0 ∫ 0 1 ( 1 − x 5 0 ) 1 0 1 1
x = 1 − x 5 0 5 0 1
thus x = 5 0 5 1